How to Transform the English Learning Process in a Meaningful Experience Through the Influence of the Target Language in the Students’ Local Context? (2017)
ABSTRACT: This project research was focused on how the English input that is always present in the students’ daily lives can help them to be in contact with the foreign language they want to learn. The main objective was to explore how this exposure to an authentic form of the language can help them to deal better with the school content resulting not only in an increase of their performance but also in the building of a meaningful learning experience. Through the development of this project it was also aimed to help the students to become aware of the implications of the use of a foreign language in their local context and to foster a reflective attitude towards them. Key words: Linguistic landscape, authentic materials, meaningful learning, critial thinking, local context.